2007
DOI: 10.1161/hypertensionaha.107.096115
|View full text |Cite
|
Sign up to set email alerts
|

Novel Regulatory Effect of Angiotensin II Type 1 Receptor-Interacting Molecule on Vascular Smooth Muscle Cells

Abstract: Abstract-We have recently cloned a novel molecule that interacts with the angiotensin II type 1 receptor (AT1R)-associated protein (ATRAP).In this study, we tested the hypothesis that ATRAP modulates angiotensin II-induced responses in vascular smooth muscle cells. The results of immunoprecipitation and bioluminescence resonance energy transfer assay demonstrated a direct interaction between ATRAP and AT1R at baseline and showed that angiotensin II enhanced the interaction of these proteins Ͼ2-fold. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 19 publications
2
40
0
3
Order By: Relevance
“…These data suggest that Atrap reduces proximal tubular AT1 surface expression, as shown before by in vitro studies. 14,16,18 Enhanced AngII binding to the proximal tubule of AtrapϪ/Ϫ mice would be expected to stimulate tubular salt and water reabsorption and promote acid excretion predominantly by stimulation of the Na/H exchanger NHE-3. 20,28,29 Thus, that we found lower urinary pH in AtrapϪ/Ϫ mice in comparison with wild-type mice would be in line with increased AngII-dependent NHE-3 activity in the proximal tubule of AtrapϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that Atrap reduces proximal tubular AT1 surface expression, as shown before by in vitro studies. 14,16,18 Enhanced AngII binding to the proximal tubule of AtrapϪ/Ϫ mice would be expected to stimulate tubular salt and water reabsorption and promote acid excretion predominantly by stimulation of the Na/H exchanger NHE-3. 20,28,29 Thus, that we found lower urinary pH in AtrapϪ/Ϫ mice in comparison with wild-type mice would be in line with increased AngII-dependent NHE-3 activity in the proximal tubule of AtrapϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…15 Atrap catalyzes the internalization of the AT1 receptor in cultured vascular smooth muscle cells. 14,16 Also, Atrap inhibits AngII-mediated intracellular signaling in vitro. 17 Overall, the data suggest an inhibitory effect of Atrap on AT1 receptor function in vitro.…”
mentioning
confidence: 99%
“…IPA of SHR-specific genes revealed that prostaglandin E receptor 4 (Ptger4) is one of the candidate genes responsible for causing hypertension in SHR (12,13), as well as albumin (Alb) and chymase 1 (Cma1), in the presence of angiotensinogen (Agt) (14)(15)(16). Similar analyses of SHRSPspecific genes revealed that angiotensin II receptor-associated gene (Agtrap) interacts with FBJ osteosarcoma oncogene (Fos), and with angiotensin II receptor type-1B (Agtr1b) (17)(18)(19). These interactions play pivotal roles among SHRSP-specific genes, and since Agtrap and Agtr1b not only participate in the 'uptake of norepinephrine' and 'blood pressure', but also in the 'behavior' of 6-week-old SHRSP, the data presented in the present study reveal a close association between hypertension and ADHD.…”
Section: Introductionmentioning
confidence: 97%
“…19 -25 The results of our previous in vitro studies also showed that ATRAP suppresses Ang II-induced hypertrophic and proliferative responses by promoting a constitutive internalization of AT1R and decreasing the p38 MAPK activity in cardiovascular cells, thereby suggesting ATRAP to be an endogenous inhibitor of AT1R signaling. 6,12 In this study, it is revealed that the incubation of cardiomyocytes with Ang II as well as the chronic infusion of Ang II into Sprague-Dawley rats significantly decreased the ratio of ATRAP to AT1R through a suppression of ATRAP protein expression concomitantly with the hypertrophic responses in vitro and in vivo. We observed that olmesartan abolished Ang II-mediated decreases in the ATRAP to AT1R ratio through an upregulation of ATRAP protein expression in mice cardiomyocytes and hearts of Ang II-infused mice (Wakui and Tamura, unpublished observation).…”
Section: Discussionmentioning
confidence: 79%
“…5,6,12 The anti-AT1R antibody (sc-1173) was purchased from Santa Cruz Biotechnology, Inc. 5 Western blot analysis was performed as described previously. 5,6 Briefly, the cell extracts (20 g per lane) or rat tissue extracts (10 g per lane for liver and kidney and 20 g per lane for heart) were used for electrophoresis.…”
Section: Western Blot Analysis Of Atrap and At1rmentioning
confidence: 99%